Entrainment of brain oscillations by transcranial alternating current stimulation - Helfrich, Randolph F; Schneider, Till R; Rach, Stefan; Trautmann-Lengsfeld, Sina A; Engel, Andreas K; Herrmann, Christoph S (Current biology, 2014)
Novel methods for neuronal entrainment [1-4] provide the unique opportunity to modulate perceptually relevant brain oscillations [5, 6] in a frequency-specific manner and to study their functional impact on distinct cognitive functions. Recently, evidence has emerged that tACS (transcranial alternating current stimulation) can modulate cortical oscillations [7-9]. However, the study of electrophysiological effects has been hampered so far by the absence of concurrent electroencephalogram (EEG) recordings. Here, we applied 10 Hz tACS to the parieto-occipital cortex and utilized simultaneous EEG recordings to study neuronal entrainment during stimulation. We pioneer a novel approach for simultaneous tACS-EEG recordings and successfully separate stimulation artifacts from ongoing and event-related cortical activity. Our results reveal that 10 Hz tACS increases parieto-occipital alpha activity and synchronizes cortical oscillators with similar intrinsic frequencies to the entrainment frequency. Additionally, we demonstrate that tACS modulates target detection performance in a phase-dependent fashion highlighting the causal role of alpha oscillations for visual perception.